THE EFFECTIVENESS OF TELENURSING SI KASIH (SISTEM INFORMASI KONDISI PASIEN HARIAN) ON ANXIETY OF THE FAMILY OF ISOLATED COVID-19 PATIENTS - eviwindha suara; Zuhrotun Aliyah (Jurnal Ilmu Keperawatan Medikal Bedah, 2022)
This study was held to see the effect of Sikasih Telenursing on the anxiety of the patient's family in the Covid 19 isolation room. Sikasih (sistem informasi kondisi pasien harian) is one of the telenursing services that provides information on the patient's condition. This study uses a quantitative approach with a quasi-experimental research design in one group (one-group pre-post test design without control). The population of this study was the family of patients who were treated in the COVID-19 isolation room, the sample used was 18 respondents. The instrument for measuring anxiety is the Zung Self-Rating Anxiety Scale. The results of data analysis showed that telenursing sikasih (sistem informasi kondisi pasien harian)  was effective in reducing the anxiety of the patient's family, with p value (0.014) on the third day and p value (0.020) on the fifth day.